Assessment of Diversity of Antimicrobial Resistance Phenotypes and Genotypes of Mannheimia haemolytica Isolates From Bovine Nasopharyngeal Swabs - Carter, Hannah F.; Wills, Robert W.; Scott, Matthew A.; Thompson, Alexis C.; Singer, Randall S.; Loy, John Dustin; Karisch, Brandi B.; Epperson, William B.; Woolums, Amelia R. (Frontiers in Veterinary Science, 2022)
The threat of bovine respiratory disease (BRD) for cattle operations is exacerbated by increasing prevalence of antimicrobial resistance (AMR) in Mannheimia haemolytica, a leading cause of BRD. Characterization of AMR in M. haemolytica by culture and susceptibility testing is complicated by uncertainty regarding the number of colonies that must be selected to accurately characterize AMR phenotypes (antibiograms) and genotypes in a culture. The study objective was to assess phenotypic and genotypic diversity of M. haemolytica isolates on nasopharyngeal swabs (NPS) from 28 cattle at risk for BRD or with BRD. NPS were swabbed onto 5 consecutive blood agar plates; after incubation up to 20 M. haemolytica colonies were selected per plate (up to 100 colonies per NPS). Phenotype was determined by measuring minimum inhibitory concentrations (MIC) for 11 antimicrobials and classifying isolates as resistant or not. Genotype was indirectly determined by matrix-assisted laser desorption/ionization time of flight mass spectroscopy (MALDI-TOF MS). NPS from 11 of 28 cattle yielded at least one M. haemolytica isolate; median (range) of isolates per NPS was 48 (1-94). NPS from 7 cattle yielded one phenotype, 3 NPS yielded two, and 1 NPS yielded three; however, within a sample all phenotypic differences were due to only one MIC dilution. On each NPS all M. haemolytica isolated were the same genotype; genotype 1 was isolated from 3 NPS and genotype 2 was isolated from 7. Diversity of M. haemolytica on bovine NPS was limited, suggesting that selection of few colonies might adequately identify relevant phenotypes and genotypes.